Training workshops on Participatory Integrated Climate Services for Agriculture (PICSA) - Dembélé, Catherine; Bazie, Paulin (World Agroforestry Centre, 2021)
Base on the experience of Participatory Integrated Climate Services for Agriculture (PICSA) implementation in West Africa, ICRAF is suggesting linking value chains (VCs) development, innovation platform elaboration with PICSA approach as a mean for climate change adaptation and mitigation and enhancing farmers’ resilience. This aims to integrating PICSA to the planned activities of partners such as CORAF through their existing innovation platforms and use the developed skills to improve the efficiency of the most important VCs while reducing risks. By strengthening the capacities of actors on climate change adaptation, skills acquired from PICSA trainings can also be considered as de-risking avenue in agriculture-food systems-value chains and thus provide more possibilities for these skilled persons to access financial services for their livelihood activities. PAIRED, an USAID funded project of CORAF, has been seen as excellent opportunity for linking PICSA to VCs development through Innovation Platform in West Africa. ICRAF has then engaged in collaboration with CORAF to achieve this goal. The training started in Kumasi, Ghana for 21 participants including three women coming from Ghana and Nigeria, the two West African Anglophone countries (Ghana and Nigeria) involved in CORAF/PARIED project from May 17 to 21, 2021. The second session was held in Cotonou, Benin from May 31 to June 4, 2021 for 4 Francophone countries including Benin, Mali, Niger and Senegal. Twentyfour participants (1 woman), coming from meteorological services agencies, state extension services and national research institutes, attended the francophone workshop in Cotonou. PAIRED is a West African Agricultural Research, Education and Development Partnership project funded by USAID for 6 years (2017-2022) led by CORAF, an international non-profit association working to enhance prosperity, food, and nutrition security in West and Central Africa with a headquarter based in Dakar, Senegal. CORAF has been a partner of ICRAF for various projects such as Capacitating Stakeholders in Using Climate Information for Enhanced Resilience in the Agricultural Sector in West Africa (CASCIERA-TA) a two-year World Bank funded project (Bayala et al. 2020). PAIRED project is implemented in 6 West African countries including Benin, Ghana, Mali, Niger, Nigeria, and Senegal. The main objective is to increase agricultural growth, food and nutritional security and reduce poverty in West and Central Africa through innovation platforms and the diffusion and adoption of innovative technologies. There is component regarding the diffusion included for addressing the challenges of climate change and variability that farmers are facing, it assumed that synergies between climate change adaptation goals and competitive strategies in food value chains, resilience of the food systems are of great importance. To help farmers copping with the negative impact of climate change CORAF and ICRAF are collaborating with various partners including AGRHYMET, Climate Change Agriculture and Food Security research program (CCAFS), the University of Reading, national meteorological and hydrological services, national research institutes and various NGOs in many West African countries to implement innovative approaches such climate-smart agriculture (CSA), Climate-Smart Village (CSV) and Participatory Integrated Climate Services for Agriculture (PICSA). The goal of the present activitiesis to build the capacity of agriculture stakeholders in the use of climate information services and strengthen the value chains of essential livelihood products in West Africa for innovative public-private joint venture. This requires identifying market and primary entry points through PICSA as well as extending the participation in the value chains to corporate partners alongside civil society, smallholder farmers and research institutions. The specific objective of these 2 session trainings is to enhance the capacity of stakeholders involved in PAIRED project to learn and implement 4 PICSA approach for an efficient use of climate information services and increase farmers’ resilience to climatic change.